2006
DOI: 10.1385/mb:32:2:159
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Separation Principles in Chromatographic and Electromigration Techniques

Abstract: Almost half of the drugs in use today are chiral. It is well established that the pharmacological activity is mostly restricted to one of the enantiomers (eutomer). There can be qualitative and quantitative differences in the activity of the enantiomers. In many cases, the inactive enantiomer (distomer) shows unwanted side effects or even toxic effects. Even if the side effects are not that drastic, the distomer has to be metabolized and this represents an unnecessary burden for the organism. Therefore, the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
56
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(58 citation statements)
references
References 134 publications
0
56
0
2
Order By: Relevance
“…Some examples of chiral selectors include: surfactant aggregates, CDs, crown ethers, and glycopeptides. Due to the vast exploration in this subject, numerous reviews detailing fundamentals and applications can be found in the literature prior to 2005 [6][7][8][9][10][11] and over the past two years [12][13][14][15]. Reviews have also covered methods developed specifically for pharmaceutical compounds [16][17][18][19][20][21][22], biological compounds [23], chiral LC-MS/ CE-MS [24], pesticides [25], pollutants [26], and food additives [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Some examples of chiral selectors include: surfactant aggregates, CDs, crown ethers, and glycopeptides. Due to the vast exploration in this subject, numerous reviews detailing fundamentals and applications can be found in the literature prior to 2005 [6][7][8][9][10][11] and over the past two years [12][13][14][15]. Reviews have also covered methods developed specifically for pharmaceutical compounds [16][17][18][19][20][21][22], biological compounds [23], chiral LC-MS/ CE-MS [24], pesticides [25], pollutants [26], and food additives [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…This implies the development of chiral sorting strategies that correspond to the ability to separate two entities that only differ by their handedness. Established chiral separation techniques at molecular scale are mostly based on the recognition of material chirality by another material that is designed to distinguish between the left-and right-handed versions of the entity to be sorted 1,2 . Instead, passive approaches free from such chiral recognition may also be considered, for instance by relying on transport phenomena, as discussed in the early 70s 3 .…”
mentioning
confidence: 99%
“…As these forms often have profoundly different impacts on human body, drug-regulating authorities require them to be separated and tested individually on toxicity and therapeutic efficacy [3][4][5]. The detection of enantiomeric forms of chiral molecules is only possible through their interaction with other chiral objects [6][7][8]. Semiconductor nanocrystals, which are often intrinsically chiral because of the unavoidable surface and bulk defects, are objects of particular promise owing to their distinctive photoluminescence properties [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%